IMPLEMENTASI PROGRAM 3R (REDUCE, REUSE, RECYCLE) DALAM MENUMBUHKAN KARAKTER PEDULI LINGKUNGAN SISWA KELAS V SEKOLAH DASAR NEGERI CIPETE 3 KOTA TANGERANG - Virna Dhia Ulhaq; Ferry Perdiansyah; Mawardi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of the 3R Program (Reduce, Reuse, Recycle) in fostering environmental awareness among fifth-grade students at Cipete Public Elementary School in Tangerang City. The study employed a qualitative descriptive method with data collection techniques including observation, interviews, and documentation. The results of the study indicate that the 3R Program has been implemented through activities such as reducing plastic use, reusing items that are still in good condition, and sorting and processing waste. The program plays a role in fostering students’ environmentally conscious character, as demonstrated by habits such as maintaining cleanliness, disposing of waste according to type, and conserving water and electricity. Thus, the implementation of the 3R Program at Cipete 3 in Tangerang City has been successful and supports the development of students’ environmentally conscious character.